(untitled) (Applied Biological Research, 2017)
The Smc5/6 protein complex inhibits the replication of hepatitis B virus (HBV) by an unknown mechanism. HBx, the regulatory protein of HBV, binds Smc5/6, promotes its ubiquitination by recruiting it to DDB1-CRL4 E3 ubiquitin ligase and mediates proteasomal degradation. In absence of HBx, Smc5/6 complex binds to cccDNA of HBV and inhibits transcription and replication of HBV. Thus Smc5/6 complex acts antagonistically to HBV infection. This could aid in the development of potential therapeutics against HBV infection. In this minireview, the role of Smc5/6 in replication and its interaction with HBx protein of HBV is discussed.